(3NdGUI GdCOH aj GdQO Ydi ef bGd(B: (3Ef TQa GdYde CaVd ef TQa GdfSHs - (3eMeO GdegOj Hf eMeO GdUNQGhj GdbGHSj GdCfOdSjs
(3ChdgG (B:s
(3hHYO(B: (3abO PcQ dj HYV GdENhGf ef Cgd GdHjJ Cfg LQi cdGe Hjfg hHjf SGOGJfG GdWdHI Ydi Cf bGd dg GdWGdH(B: (3Ef TQa GdYde CaVd ef TQa GdfSH aQO Ydjg GdTQja HCf TQa GdfSH CaVd ef TQa GdYde s
(3BNQgG (B:s
(3fSCd Gddg JYGdi Cf jSGeMfG aj Mbge Bejf Efg Ydi Pdc bOjQ hHGdELGHI LOjQ, dG Edg ZjQg hdG NjQ EdG NjQg hgh fYe Gdehdi hfYe GdfUjQ s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B289 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdCOHs